Coated diaphragm and preparation method thereof
By using polymers with side chains replaced by anion side groups and appropriate phase separation technology on the lithium battery separator, the problems of insufficient thermal stability and electrolyte wetting are solved, and efficient lithium ion migration and lithium dendrites are achieved. Suppression improves battery safety and energy density.
Patent Information
- Application Number
- CN202310962142.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium battery separators have poor thermal stability at high temperatures and insufficient electrolyte wetting, resulting in low number of lithium ions migration, which can easily induce the growth of lithium dendrites, reduce the energy density and circulation performance of the battery, and also pose safety hazards.
The polymer with side chains replaced by anionic side groups as the component of the coating layer is prepared with phase separation methods of steam phase separation and non-solvent phase separation to prepare a porosity of 52% to 80% and a pore size of not less than 10 nm. Coated diaphragm.
It improves the thermal stability and electrolyte affinity of the lithium battery separator, enhances the number of lithium ions migration, effectively inhibits the electroplating and dendrite growth of lithium, and improves the safety performance and energy density of the battery.
Smart Images

Figure CN119447697A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium battery technology, and in particular to a coated diaphragm and a preparation method thereof. Background Art
[0002] In recent years, the application of lithium batteries has become increasingly widespread. The miniaturization and lightweight of mobile devices, the development of new energy vehicles and the construction of large-scale power networks have put forward higher requirements for the energy density and cycle performance of batteries, and the safety issues of battery use have also become increasingly prominent. High safety and high performance have become the mainstream development direction of lithium batteries.
[0003] The diaphragm is one of the key materials of lithium batteries. The pores of the diaphragm provide channels for the migration of lithium ions during the charge and discharge process of the battery, and isolate the positive and negative electrodes to prevent internal short circuits in the battery. The structure and performance of the diaphragm directly determine the cycle life, safety, energy density and power density of the battery. Currently, most commonly used commercial diaphragms are polyolefin diaphragms. However, commercial diaphragms have the following problems: (1) The thermal stability of the diaphragm is poor. When the internal temperature of the battery rises, severe thermal shrinkage behavior will occur, causing thermal runaway of the battery; (2) The affinity between the diaphragm and the electrolyte is poor. Incomplete infiltration of the electrolyte during the battery assembly process will cause uneven lithium ion migration, resulting in spatially uneven lithium deposition or lithium intercalation, inducing the growth of lithium dendrites. At the same time, poor electrolyte wettability will also increase the cost of the battery assembly process; (3) The commonly used diaphragm matrix material is non-polar polyolefin, and the lithium ion migration number in the entire diaphragm / electrolyte system is low, which easily induces lithium plating and dendrite growth, ultimately reducing energy density and cycle performance, and also brings safety hazards. Solutions to the above problems include developing new diaphragms and coating the diaphragm surface.
[0004] Surface coating of the diaphragm is a common solution. At present, the surface coating of the diaphragm mainly includes two methods: one is to coat the surface of the diaphragm with inorganic materials. For example, there is a solution that proposes to use ceramic coating on the surface of the diaphragm, which enhances the electrolyte absorption capacity of the diaphragm. The coating of ceramic materials greatly increases the thermal stability and electrolyte affinity of the diaphragm. However, the high mass density of ceramic materials will lead to a decrease in the overall energy density of the battery. At the same time, the coated alumina layer cannot increase the number of lithium ion migration during battery operation. The second is to coat the surface of the polyolefin diaphragm with polymer materials. For example, there is a solution that proposes to use a surface-modified PMMA / PVDF mixed coating on the surface of the diaphragm, which enhances the electrolyte absorption capacity of the diaphragm and improves the ionic conductivity, but it is difficult to increase the number of lithium ion migration. There is also a proposal to use surface-modified polyaryletherketone to coat the surface of the diaphragm. The coating of polyaryletherketone gives the diaphragm excellent thermal stability and electrochemical properties. However, the preparation process includes chemical treatment of the diaphragm and uses strong acid as a solvent, which increases the complexity and danger of the process. At the same time, although the tortuous structure improves the electrochemical performance, it is still difficult to fundamentally suppress dendrites by regulating the pores. Summary of the invention
[0005] The purpose of the present application is to provide a coated diaphragm and a preparation method thereof, so as to improve the problem that the current coated diaphragm is prone to generate lithium dendrites.
[0006] In the first aspect, an embodiment of the present application provides a coated membrane, which includes: a base membrane and a coating layer, the coating layer is attached to at least a portion of the base membrane, the coated membrane has a porosity of 52% to 80%, the pore structure of the coating layer has a pore size of not less than 10 nm, and the coating layer includes a polymer whose side chains are substituted by anionic side groups.
[0007] In the above implementation process, since the pore structure of the coating layer has a relatively suitable pore size and porosity, ions can be better transported in the pore structure, which can reduce the risk of lithium plating and dendrite growth, and improve the problem of lithium dendrites easily generated in the current coated diaphragm. At the same time, the anion side group can effectively inhibit the migration of anions and accelerate the migration of cations. When assembled into a battery, it can further increase the number of lithium ion migrations in the diaphragm / electrolyte system, effectively inhibit lithium plating and dendrite growth, and reduce the internal polarization of the battery, thereby improving the safety performance and energy density of the battery.
[0008] As an optional embodiment, the anionic side groups include -COOLi and / or -SO3Li.
[0009] As an optional embodiment, the polymer is a polar polymer; or the polymer is polyetheretherketone. The polymer is a polar polymer, which has good affinity with the electrolyte and can achieve full wetting of the coated separator after being assembled into a battery.
[0010] As an optional embodiment, the structural formula of the polymer whose side chain is substituted by anionic side groups is:
[0011]
[0012] Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and optionally, n / (n+m)=0.3-1.
[0013] The polymer formed by replacing the side chain of polyetheretherketone with -COOLi and -SO3Li has high thermal stability and can effectively reduce the shrinkage of the coated diaphragm under heat. At the same time, its mass density is small, which can reduce the influence of the coating on the battery energy density to a greater extent. At the same time, n / (n+m)=0.3-1 is controlled to facilitate the dissolution of the substance in the polar organic solvent and the preparation of the coating slurry in the subsequent preparation of the slurry.
[0014] As an optional implementation, in the coating layer, the mass proportion of the polymer whose side chains are substituted by anionic side groups is 5%-90%.
[0015] The mass proportion of polymers whose side chains are substituted by anionic side groups in the coating layer is generally positively correlated with the improvement of the effect of the coated membrane. The larger the mass proportion, the more obvious the improvement in the performance of the coated membrane.
[0016] As an optional implementation, the coating layer has a thickness of 0.5-20 μm.
[0017] The thickness will affect the length of the migration path of lithium ions. Generally speaking, the smaller the thickness of the coating layer, the shorter the migration path of lithium ions, which can reduce the impact on their migration; at the same time, the smaller the thickness, the smaller the loss of the coating layer, which effectively saves the preparation cost of the coated diaphragm. Conversely, the thicker the coating layer, the greater the amount of polymer used, which also affects ion migration. Under the premise of not affecting the migration of lithium ions, increasing the thickness of the coating layer can improve the performance of the diaphragm. In addition, when the thickness is less than 0.5μm or greater than 20μm, the requirements for slurry coating and dispersion process are also high.
[0018] As an optional embodiment, the coating layer also includes a binder. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyetherimide, polyisophthalamide and polyparaphenylene terephthalamide; and / or the base membrane is a polypropylene microporous diaphragm, a polyethylene microporous diaphragm or a polypropylene / polyethylene / polypropylene three-layer composite microporous diaphragm.
[0019] On the one hand, the addition of the binder solves the problem of poor adhesion between the polymer whose side chains are substituted by anionic side groups and the base membrane, and the base membrane does not need to be treated to achieve the coating of the ionized polyetheretherketone; on the other hand, the polymer whose chains are substituted by anionic side groups and are easily swellable in the coating layer can be confined. After being assembled into a battery, the change of the pore structure during the operation of the battery can be avoided, and good performance can be maintained at all times. It can also avoid the collapse of the coating layer structure during the operation of the battery and maintain the effectiveness of the battery; in addition, the introduction of the binder can also reduce the cost of coating the diaphragm to a certain extent.
[0020] In a second aspect, an embodiment of the present application provides a coated diaphragm, the coated diaphragm comprising: a base film and a coating layer, the coating layer being attached to at least a portion of the base film; the coated diaphragm has a porosity of 52% to 80%, and the pore size range of the pore structure of the coating layer is not less than 10 nm; the coating layer comprises a polymer whose side chain is substituted by anionic side groups, and the structural formula of the polymer whose side chain is substituted by anionic side groups is:
[0021]
[0022] Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and n / (n+m)=0.3-1.
[0023] In the above implementation process, the coated diaphragm has high thermal stability and good electrolyte affinity, and can effectively inhibit anion migration and increase the lithium ion migration number of the coated diaphragm / electrolyte system. When n / (n+m) is less than 0.3, the polymer is difficult to dissolve in the solvent, so it is difficult to form a uniform coating, thereby affecting the preparation of the coated diaphragm.
[0024] In a third aspect, an embodiment of the present application provides a method for preparing a coated diaphragm, the method comprising:
[0025] Applying the coating slurry to the surface of the base film to obtain a solution-coated diaphragm;
[0026] Phase separation is performed on the solution-coated diaphragm to replace the good solvent in the coating slurry, and then drying is performed to obtain a coated diaphragm including a coating layer;
[0027] Wherein, the phase separation is a combination of steam-induced phase separation and non-solvent-induced phase separation; the coating slurry includes a polymer whose side chains are substituted by anionic side groups, and further, the anionic side groups include -COOLi and / or -SO3Li.
[0028] By adopting the above design, a phase separation method of steam-induced phase separation combined with non-solvent-induced phase separation is utilized, so that the entire coating layer has a porous structure, especially the surface layer also has a porous structure for improving ion transport. After the prepared coated diaphragm is assembled into a battery, better ion transport is achieved in the porous structure, which can reduce the risk of lithium electroplating and dendrite growth, thereby achieving the purpose of improving the problem of the current coated diaphragm being prone to the generation of lithium dendrites.
[0029] As an optional embodiment, the humidity of steam-induced phase separation is 30%-95%, and the time of steam-induced phase separation is 10-300s; the poor solvent for non-solvent-induced phase separation includes at least one of water, ethanol, isopropanol, n-pentanol, ethyl acetate and dichloromethane.
[0030] The pore structure of the surface layer of the coating layer can be controlled by adjusting the humidity and time of steam-induced phase separation, as well as the type of non-solvent in non-solvent-induced phase separation, the temperature of the casting liquid and other conditions.
[0031] As an optional embodiment, the coating slurry comprises a polyetheretherketone whose side chains are substituted by lithium sulfonate-containing side groups or a polyetheretherketone whose side chains are substituted by lithium carboxylate-containing side groups.
[0032] The preparation method of the polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group comprises: subjecting the polyetheretherketone to a sulfonation reaction with sulfuric acid to obtain a sulfonated polyetheretherketone; subjecting the sulfonated polyetheretherketone to a lithium salt reaction with lithium hydroxide to obtain a polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group. The sulfonation of the polyetheretherketone is achieved by a one-step modification method, which is simple and economical.
[0033] The preparation method of polyetheretherketone whose side chain is substituted by lithium carboxylate-containing side groups comprises: subjecting 4,4'-difluorobenzophenone, hydroquinone, methyl hydroquinone and potassium carbonate to an aromatic nucleophilic substitution reaction to obtain polyetheretherketone containing methyl groups; subjecting the polyetheretherketone containing methyl groups to a substitution reaction to obtain polyetheretherketone containing dibromomethyl groups; subjecting the polyetheretherketone containing dibromomethyl groups to a temperature-raising reaction to obtain polyetheretherketone containing aldehyde groups; subjecting the polyetheretherketone containing aldehyde groups to an oxidation reaction to obtain carboxylated polyetheretherketone; subjecting the carboxylated polyetheretherketone to a lithium salt reaction with lithium hydroxide to obtain polyetheretherketone whose side chain is substituted by lithium carboxylate-containing side groups.
[0034] As an optional implementation, the mass proportion of the solvent in the coating slurry is 50%-90%.
[0035] The higher the proportion of the solvent, the easier it is to disperse the solute evenly, so that the solute can be evenly coated on the base film. However, the higher the proportion of the solvent, the less the relative solute content, and it is difficult to ensure the amount of solute attached to the base film.
[0036] In a fourth aspect, an embodiment of the present application provides a lithium battery, which includes the coated diaphragm of the first aspect or the second aspect or a coated diaphragm prepared by the method for preparing the coated diaphragm of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0039] Figure 1 This is a SEM image of the coating layer of the coated diaphragm provided in Example 1 of the present application;
[0040] Figure 2 The cyclic discharge capacity curve of a battery assembled with the coated diaphragm provided in Example 1 of the present application and a diaphragm purchased from the market;
[0041] Figure 3 A lithium ion migration graph of the coated diaphragm provided in Example 1 of the present application;
[0042] Figure 4 This is a comparison chart of the results of the coated diaphragm provided in Example 1 of the present application and the diaphragm purchased from the market after being heated at room temperature and at 130° C. for 1 hour;
[0043] Figure 5 A comparison chart of contact angle test results of the coated diaphragm provided in Example 1 of the present application and a diaphragm purchased from the market;
[0044] Figure 6 The cycle capacity curves of Examples 11 and 12 of the present application and the separators purchased from the market are respectively assembled in lithium metal batteries;
[0045] Figure 7 A flowchart of a method provided in an embodiment of the present application;
[0046] Figure 8 This is a SEM image of the coated membrane provided in Example 7 of the present application. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0048] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0049] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0050] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.
[0051] An embodiment of the present application provides a coated membrane, which includes: a base membrane and a coating layer, the coating layer is attached to at least a portion of the base membrane, the coated membrane has a porosity of 52% to 80%, the pore structure of the coating layer has a pore size range of not less than 10 nm, and the coating layer includes a polymer whose side chains are substituted by anionic side groups.
[0052] The base membrane generally has pores, which provide channels for the migration of lithium ions during the charge and discharge process of the battery. At the same time, the base membrane serves to isolate the positive and negative electrodes and avoid internal short circuits in the battery. Usually, the base membrane can be a polyolefin separator; illustratively, the polyolefin separator can be selected from a polypropylene separator, a polyethylene separator, and a polypropylene / polyethylene / polypropylene three-layer composite separator.
[0053] The coating layer is a functional layer attached to the base membrane, which is mainly used to solve the problems of poor wettability of the base membrane to the electrolyte, low liquid retention rate, obvious concentration polarization during the cycle, and serious lithium dendrite growth. Usually, in addition to the active ingredients, the coating layer also contains a binder, which mainly plays the role of adhering the active ingredients to the base membrane. The binder can be an oily binder or an aqueous binder. Exemplarily, the oily binder can be selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer and polyimide; the aqueous binder can be selected from at least one of polyacrylic acid binders, polyurethane binders, polyacrylonitrile binders, polyacrylate binders, carboxymethyl cellulose lithium binders, carboxylated chitosan binders, styrene-butadiene emulsions and polytetrafluoroethylene emulsions.
[0054] The coating layer being attached to at least a portion of the base film means that the coating layer is attached to a portion of or the entire surface of the base film. At the same time, the coating layer may be attached to only one side of the base film, or to both sides of the base film at the same time.
[0055] The pore structure refers to a structure formed by a system composed of multiple pores, and there may be a relationship of interconnection between the pores. The pore size range of the pore structure is not less than 10nm. Optionally, the pore size range of the pore structure is not less than 100nm, the pore size range of the pore structure is not less than 300nm, the pore size range of the pore structure is not less than 500nm, the pore size range of the pore structure is not less than 700nm, the pore size range of the pore structure is not less than 900nm, the pore size range of the pore structure is not less than 1100nm, the pore size range of the pore structure is not less than 1300nm, the pore size range of the pore structure is not less than 1500nm, the pore size range of the pore structure is not less than 1700nm, and the pore size range of the pore structure is not less than 2000nm. Optionally, the pore size range of the pore structure is 10nm to 10μm. Preferably, the pore size range of the pore structure is 10nm to 2μm. The pore size is negatively correlated with the lithium ion migration number to a certain extent. The larger the pore size, the smaller the lithium ion migration number. However, when the pore size is too small, it will affect the path of ion passage. The inventors believe that when the pore size is in the range of 10nm to 10μm, there can be a more appropriate lithium ion migration number.
[0056] Porosity refers to the percentage of pore volume in a bulk material to the total volume of the material in its natural state.
[0057] In the above implementation process, since the pore structure of the coating layer has a relatively suitable pore size and porosity, ions can be better transported in the pore structure, which can reduce the risk of lithium plating and dendrite growth, and achieve the purpose of improving the problem of lithium dendrites that are easy to be generated in the current coated diaphragm. At the same time, the anion side group can effectively inhibit the migration of anions and accelerate the migration of cations. When assembled into a battery, it can further increase the number of lithium ion migrations in the diaphragm / electrolyte system, effectively inhibit the plating and dendrite growth of lithium, and reduce the internal polarization of the battery, thereby improving the safety performance and energy density of the battery.
[0058] In some embodiments, the anionic side groups may be selected from -COOLi and / or -SO3Li. It will be appreciated by those skilled in the art that -COOLi and / or -SO3Li may be directly connected to the main chain of the polymer, and may also be indirectly connected to the main chain of the polymer through other groups. The polymer may be selected from polar polymers. The polymer adopts polar polymers and has good affinity with the electrolyte. After being assembled into a battery, sufficient wetting of the coated diaphragm can be achieved. Further, the polymer is selected from polyetheretherketone.
[0059] In some embodiments, the polymer having side chains substituted with anionic side groups has the structural formula:
[0060]
[0061] Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and optionally, n / (n+m)=0.3-1.
[0062] The polymer formed by using -COOLi and -SO3Li to replace the side chain of polyetheretherketone has high thermal stability and can effectively reduce the shrinkage of the coated diaphragm under heat. At the same time, its mass density is small, which can reduce the impact of the coating on the battery energy density to a greater extent.
[0063] In some embodiments, in the coating layer, the polymer whose side chains are substituted with anionic side groups accounts for 5% to 90% by weight.
[0064] The mass proportion of the polymer whose side chains are substituted by anionic side groups is 5%-90% means that the value obtained by dividing the mass value of the polymer whose side chains are substituted by anionic side groups by the mass value of the entire coating layer is 5%-90%.
[0065] The mass proportion of polymers whose side chains are substituted by anionic side groups in the coating layer is generally positively correlated with the improvement of the effect of the coated diaphragm. The larger the mass proportion, the more fully its own characteristics can be exerted in the coating layer.
[0066] In some embodiments, the coating layer has a thickness of 0.5-20 μm.
[0067] The thickness will affect the length of the migration path of lithium ions. Generally speaking, the thinner the coating layer, the shorter the migration path of lithium ions, reducing the impact on their migration; at the same time, the thinner the thickness, the smaller the coating layer consumption, which effectively saves the preparation cost of the coated diaphragm. Conversely, the thicker the coating layer, the greater the amount of polymer used, which can further improve the performance of the coated diaphragm.
[0068] In some embodiments, the coating layer composition further includes a binder.
[0069] On the one hand, the addition of the binder solves the problem of poor adhesion between the polymer whose side chains are substituted by anionic side groups and the base membrane caused by the hydrophobicity of the base membrane material, and the base membrane does not need to be treated to achieve the coating of the ionized polyetheretherketone; on the other hand, the polymer whose chains are substituted by anionic side groups and are easily swellable in the coating layer can be confined. After being assembled into a battery, the change of the pore structure during the operation of the battery can be avoided, and good performance can be maintained at all times. It can also avoid the collapse of the coating layer structure during the operation of the battery and maintain the effectiveness of the battery; in addition, the introduction of the binder can also reduce the cost of coating the diaphragm to a certain extent.
[0070] Exemplarily, the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyetherimide, poly(meta-phenylene isophthalamide) and poly(para-phenylene terephthalamide).
[0071] The present application provides a coated diaphragm, which comprises: a base film and a coating layer, wherein the coating layer is attached to at least a portion of the base film; the coated diaphragm has a porosity of 52% to 80%, and the pore size range of the pore structure of the coating layer is not less than 10 nm; the coating layer comprises a polymer whose side chain is substituted by anionic side groups, and the structural formula of the polymer whose side chain is substituted by anionic side groups is:
[0072]
[0073] Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and n / (n+m)=0.3-1. The coated diaphragm has good thermal stability and electrolyte affinity, and can effectively inhibit anion migration and increase the lithium ion migration number of the coated diaphragm / electrolyte system.
[0074] The inventors found that the traditional non-solvent induced phase separation scheme will bring about a dense surface pore structure due to the rapid phase separation behavior on the surface of the polymer membrane during the phase separation process, which is not conducive to the transmission of ions. The inventors intend to improve the dense pore structure of the surface of the coating layer to reduce the impact on ion transmission. The scheme of vapor-induced combined with liquid-induced phase separation is adopted. By allowing the solution-coated diaphragm to stand for different periods of time under a certain humidity environment and then performing liquid-induced phase separation, the surface pore structure can be effectively regulated. At the same time, traditional diaphragms are chemically inert, the diaphragm / electrolyte system has a low lithium ion migration number, and the concentration polarization is severe, which will lead to the formation of lithium dendrites. The inventors intend to introduce anionic side groups in the coating layer to inhibit anion migration and increase the lithium ion migration number to reduce the formation of lithium dendrites.
[0075] The present application provides a method for preparing a coated diaphragm, wherein the coated diaphragm is the coated diaphragm of the first aspect or the second aspect; the method comprises:
[0076] S0. Obtain coating slurry.
[0077] In some embodiments, the coating slurry comprises a polyetheretherketone whose side chain is substituted by a lithium sulfonate side group or a polyetheretherketone whose side chain is substituted by a lithium carboxylate side group. Obtaining the coating slurry comprises dispersing the polyetheretherketone whose side chain is substituted by a lithium sulfonate side group and / or the polyetheretherketone whose side chain is substituted by a lithium carboxylate side group and a binder in a solvent.
[0078] The solvent may be specifically selected from at least one of N-methyl-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide.
[0079] In some embodiments, the weight percentage of the solvent in the coating slurry is 50%-90%. In other words, in the coating slurry, the weight percentage of the polyetheretherketone with side chains substituted by lithium sulfonate side groups or the polyetheretherketone with side chains substituted by lithium carboxylate side groups and the binder is 10%-50%.
[0080] The higher the proportion of the solvent, the easier it is to disperse the solute evenly, so that the solute can be evenly coated on the base film. However, the higher the proportion of the solvent, the less the relative solute content, and it is difficult to ensure the amount of solute attached to the base film.
[0081] In some embodiments, the mass ratio of the polyetheretherketone whose side chain is substituted with a lithium sulfonate-containing side group or the polyetheretherketone whose side chain is substituted with a lithium carboxylate-containing side group to the binder may be 5:95 to 90:10.
[0082] The method for preparing polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group comprises:
[0083] S0.11. Sulfonation reaction of polyetheretherketone and sulfuric acid is carried out.
[0084] Specifically, in this embodiment, polyetheretherketone is dissolved in concentrated sulfuric acid at room temperature, and then heated to cause sulfonation reaction, and then precipitated with deionized water and washed to neutrality to obtain sulfonated polyetheretherketone;
[0085] S0.12. Obtain sulfonated polyetheretherketone; subject the sulfonated polyetheretherketone to lithium salt reaction with lithium hydroxide to obtain polyetheretherketone whose side chains are substituted with lithium sulfonate-containing side groups.
[0086] Specifically, in this embodiment, the obtained sulfonated polyetheretherketone is reacted with an excess of lithium hydroxide, wherein the molar ratio of lithium hydroxide to sulfonic acid side groups is greater than 1 during the reaction, so that it is fully lithium-salified to obtain polyetheretherketone containing lithium sulfonate side groups. During the reaction, the ratio of lithium sulfonate side groups to the repeating units of the copolymer before the reaction is controlled to be 0.3 to 1 by adjusting the reaction time, sulfuric acid concentration, reaction temperature and feed ratio.
[0087] The above method uses a one-step modification method to achieve the sulfonation of polyetheretherketone, which is simple and economical. At the same time, the sulfonated polyetheretherketone is prepared by a polymer modification scheme, which has greater cost advantages compared to other polymers with anionic side groups.
[0088] The method for preparing polyetheretherketone whose side chain is substituted by a lithium carboxylate-containing side group comprises:
[0089] S0.21. subjecting 4,4'-difluorobenzophenone, hydroquinone, methyl hydroquinone and potassium carbonate to an aromatic nucleophilic substitution reaction to obtain a methyl-containing polyetheretherketone;
[0090] Specifically, in this embodiment, 4,4'-difluorobenzophenone, hydroquinone, methyl hydroquinone and excess potassium carbonate are dissolved in cyclopentane sulfone under an argon atmosphere to undergo an aromatic nucleophilic substitution reaction to obtain a methyl-containing polyetheretherketone copolymer. During the reaction, the ratio of methyl side groups to copolymer repeating units is controlled to be 0.3 to 1 by adjusting the feed ratio of hydroquinone and methyl hydroquinone.
[0091] S0.22. The methyl-containing polyetheretherketone is subjected to a substitution reaction to obtain a dibromomethyl-containing polyetheretherketone;
[0092] Specifically, in this embodiment, the obtained methyl-containing polyetheretherketone copolymer is dissolved in a mixed solution of dichlorobenzene and chlorobenzene, and then the chlorobenzene is evaporated at high temperature to dry the reaction mixture, and then liquid bromine is added to fully react under ultraviolet irradiation, and finally the dibromomethyl-containing polyetheretherketone copolymer is obtained after precipitation in methanol, washing and drying.
[0093] S0.23. The polyetheretherketone containing dibromomethyl group is subjected to a temperature-raising reaction to obtain a polyetheretherketone containing an aldehyde group;
[0094] Specifically, in this embodiment, the obtained dibromomethyl-containing polyetheretherketone copolymer is dissolved in N-methylpyrrolidone, water is added and the temperature is increased to react, and the polyetheretherketone copolymer containing aldehyde groups is obtained after precipitation and washing in a mixed solution of isopropanol and n-hexane.
[0095] S0.24. The aldehyde-containing polyetheretherketone is subjected to an oxidation reaction to obtain a carboxylated polyetheretherketone;
[0096] Specifically, in this embodiment, the obtained aldehyde-containing polyetheretherketone copolymer is dissolved in N-methylpyrrolidone, dimethyl sulfoxide is added, and an aqueous solution of sodium dihydrogen phosphate is added to fully react, then acidified in hydrochloric acid, and finally precipitated and washed in methanol to obtain carboxylated polyetheretherketone, and the ratio of lithium carboxylate side groups to the repeating units of the copolymer before the reaction is controlled to be 0.3 to 1.
[0097] S0.25. Carboxylated polyetheretherketone and lithium hydroxide are reacted to form a lithium salt to obtain polyetheretherketone whose side chains are substituted with lithium carboxylate-containing side groups.
[0098] Specifically, in this embodiment, the obtained carboxylated polyetheretherketone is reacted with lithium hydroxide in an amount exceeding the molar number of carboxylic acid side groups to fully convert it into lithium salt, thereby obtaining polyetheretherketone containing lithium carboxylate side groups.
[0099] S1. The coating slurry is applied to the surface of the base film to obtain a solution-coated diaphragm;
[0100] Specifically, in this embodiment, the obtained polymer solution is coated on one side or both sides of a polyolefin-based separator to obtain a solution-coated separator.
[0101] S2. Phase separation is performed on the solution-coated membrane to replace the good solvent in the coating slurry, and then drying is performed to obtain a coated membrane including a coating layer; wherein the phase separation is a combination of steam-induced phase separation and non-solvent-induced phase separation.
[0102] Specifically, in this embodiment, the obtained solution-coated membrane is phase-separated, and the specific steps are: the solution-coated membrane is placed in an environment with a humidity of 30% to 95% and allowed to stand for 10 seconds to 5 minutes, and then immersed in a polymer poor solvent. Phase separation is achieved through the above steps, and the good solvent in the porous coating layer is completely replaced. After drying, the coated membrane is obtained.
[0103] In some embodiments, the humidity of the steam-induced phase separation is 30%-95%, and the time of the steam-induced phase separation is 10-300s; the poor solvent of the non-solvent-induced phase separation includes at least one of water, ethanol, isopropanol, n-pentanol, ethyl acetate and dichloromethane. By adjusting the humidity and time of the steam-induced phase separation, as well as adjusting the type of non-solvent of the non-solvent-induced phase separation, the temperature of the casting solution and other conditions, the pore structure of the support layer and the surface layer of the coating layer can be controlled.
[0104] By adopting the above design, a phase separation method of steam-induced phase separation combined with non-solvent-induced phase separation is utilized to make the surface layer of the prepared coating layer have a porous structure. After the prepared coated diaphragm is assembled into a battery, better ion transmission is achieved in the porous structure, which can reduce the risk of lithium electroplating and dendrite growth, thereby achieving the purpose of improving the current problem of the easy generation of lithium dendrites in the coated diaphragm.
[0105] An embodiment of the present application provides a lithium battery, which includes the coated diaphragm provided above or a coated diaphragm prepared by the method for preparing the coated diaphragm provided above.
[0106] Lithium batteries can be lithium-ion batteries, lithium metal batteries, etc. Among them, lithium-ion batteries can be assembled from a coated diaphragm, a positive electrode, a graphite negative electrode, and an electrolyte; lithium metal batteries are assembled from a coated diaphragm, a positive electrode, a metallic lithium negative electrode, and an electrolyte. The positive electrode can be made of positive electrode materials such as lithium iron phosphate, lithium cobalt oxide, and lithium manganese oxide, and the coating layer of the coated diaphragm can face the positive electrode or the negative electrode of the battery.
[0107] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0108] Examples 1-18
[0109] A method for preparing a coated diaphragm, the method comprising:
[0110] (1) dissolving polyetheretherketone in concentrated sulfuric acid at room temperature, then heating it to cause a sulfonation reaction, then precipitating it with deionized water and washing it to neutrality to obtain a sulfonated polyetheretherketone having a molar ratio of sulfonic acid side groups to repeating units before the reaction of 1;
[0111] (2) reacting the sulfonated polyetheretherketone obtained in step (1) with an excess of lithium hydroxide, wherein the molar ratio of the lithium hydroxide added during the reaction to the sulfonic acid side groups is greater than 1, so that the polyetheretherketone is fully lithium-salified to obtain a polyetheretherketone containing lithium sulfonate side groups;
[0112] (3) dissolving the sulfonated polyetheretherketone containing lithium sulfonate side groups obtained in step (2) and a binder in N-methyl-pyrrolidone to obtain a polymer solution;
[0113] (4) coating the polymer solution obtained in step (3) on one side of a polyolefin separator to obtain a solution-coated separator;
[0114] (5) subjecting the solution-coated diaphragm obtained in step (4) to vapor-induced and liquid-induced phase separation. The specific steps are as follows: placing the solution-coated diaphragm under a certain humidity environment and leaving it to stand for a period of time, and then immersing it in a poor solvent for the polymer. Phase separation is achieved through the above steps, and the good solvent in the porous coating layer is completely replaced. After drying, the coated diaphragm is obtained.
[0115] Examples 19-21
[0116] A method for preparing a coated diaphragm, the method comprising:
[0117] (1) dissolving 4,4'-difluorobenzophenone, hydroquinone, methyl hydroquinone and excess potassium carbonate in sulfolane under an argon atmosphere to undergo an aromatic nucleophilic substitution reaction to obtain a methyl-containing polyetheretherketone copolymer, and controlling the ratio of methyl side groups to the repeating units of the copolymer by adjusting the feed ratio of hydroquinone and methyl hydroquinone;
[0118] (2) dissolving the methyl-containing polyetheretherketone copolymer obtained in step (1) in a mixed solution of dichlorobenzene and chlorobenzene, then distilling off the chlorobenzene at high temperature to dry the reaction mixture, then adding liquid bromine, reacting fully under ultraviolet irradiation, and finally precipitating in methanol, washing and drying to obtain a dibromomethyl-containing polyetheretherketone copolymer;
[0119] (3) dissolving the dibromomethyl-containing polyetheretherketone copolymer obtained in step (2) in N-methylpyrrolidone, adding water and heating to react, and precipitating and washing in a mixed solution of isopropanol and n-hexane to obtain a polyetheretherketone copolymer containing an aldehyde group;
[0120] (4) dissolving the aldehyde-containing polyetheretherketone copolymer obtained in step (3) in N-methylpyrrolidone, adding dimethyl sulfoxide and an aqueous solution of sodium dihydrogen phosphate, reacting sufficiently, then acidifying in hydrochloric acid, and finally precipitating and washing in methanol to obtain a carboxylated polyetheretherketone, and controlling the molar ratio of the carboxylic acid side group to the repeating unit;
[0121] (5) reacting the carboxylated polyetheretherketone obtained in step (4) with an excess of lithium hydroxide, wherein the molar ratio of lithium hydroxide to carboxylic acid side groups is greater than 1 during the reaction, so that the polyetheretherketone is fully lithium-salified to obtain a polyetheretherketone containing lithium carboxylate side groups;
[0122] (6) dissolving the polyetheretherketone containing lithium carboxylate side groups obtained in step (5) and a binder in dimethyl sulfoxide to obtain a polymer solution;
[0123] (7) coating the polymer solution obtained in step (6) on both sides of the polyethylene microporous membrane to obtain a solution-coated membrane;
[0124] (8) subjecting the solution-coated diaphragm obtained in step (7) to vapor-induced and liquid-induced phase separation. The specific steps are as follows: placing the solution-coated diaphragm in a certain humidity environment and leaving it to stand for a period of time, and then immersing it in a poor solvent for the polymer. Phase separation is achieved through the above steps, and the good solvent in the porous coating layer is completely replaced. After drying, the coated diaphragm is obtained.
[0125] The polymer poor solvent used in the liquid-induced phase separation process in each embodiment is dichloromethane, the base film thickness is 19 μm, and other main parameter controls are shown in Table 1:
[0126]
[0127]
[0128]
[0129] Comparative Example 1
[0130] The 19 μm polyethylene microporous membrane purchased from Shenzhen Xingyuan Material Technology Co., Ltd. was not coated and was a wet-process biaxially stretched single-layer polyethylene membrane.
[0131] The coating layer of the coated diaphragm provided in each embodiment was subjected to an electron microscope scanning test. Since the results are similar, only the SEM result of the coating layer provided in Example 1 is used for illustration. Figure 1 As shown, Figure 1 This is a SEM image of the coating layer provided in Example 1 of the present application. It can be seen from the image that the coating layer has a rich pore structure.
[0132] The diaphragms provided in the embodiments and comparative examples were respectively assembled into lithium metal batteries, and the cycle capacity curves of the lithium metal batteries were tested. Since the results are similar, only the cycle capacity curves of the diaphragms provided in embodiment 1 and comparative example 2 are shown. Figure 2 As shown, it is the cyclic discharge capacity curve of the battery assembled with the coated diaphragm provided in Example 1 and the diaphragm purchased from the market. It can be seen from the figure that compared with the lithium metal battery using the polyethylene microporous diaphragm, the lithium metal battery using the coated diaphragm obtained in Example 1 has better cycle performance.
[0133] The coated separator provided in Example 1 was tested for lithium ion migration number. The results are as follows: Figure 3 As shown in the figure, it can be seen that the lithium ion migration number of the coated diaphragm provided in Example 1 is as high as 0.52.
[0134] The diaphragms provided in Example 1 and Comparative Example 1 were subjected to a thermal stability test. Specifically, the state of the diaphragm at room temperature was compared with the state after heating at 130° C. for 1 hour. The optical photographs of the test process are shown in FIG. Figure 4 As shown in the figure, it can be seen that the coated membrane exhibits higher thermal dimensional stability at high temperatures compared with the commercial membrane.
[0135] The contact angle test was performed on the membranes provided in Example 1 and Comparative Example 1. The test results are as follows: Figure 5 As shown in the figure, it can be seen that compared with the commercial membrane, the coated membrane has a smaller contact angle with the electrolyte and has better affinity with the electrolyte.
[0136] The separators provided in Examples 11 and 12 and Comparative Example 1 were respectively assembled in lithium metal batteries, and the lithium metal batteries were tested for cycle capacity. The results are as follows: Figure 6 As shown in the figure, it can be seen that compared with the lithium metal battery using the polyethylene microporous diaphragm, the lithium metal battery using the coated diaphragm has better cycle performance, and compared with Example 11, the cycle performance of the coated diaphragm obtained in Example 12 is improved after the thickness is increased, and the discharge specific capacity is slightly reduced. The increase in thickness will increase the internal impedance to a certain extent and reduce the volume energy density. Therefore, the thickness of the coating layer needs to be weighed to make the overall performance of the battery higher.
[0137] The coating layer of the diaphragm provided in each embodiment and comparative example is tested, and the test includes:
[0138] Porosity and pore size detection: The test is carried out using the mercury injection method.
[0139] Electrolyte contact angle detection: An optical contact angle meter is used to test the contact angle of 5 μL electrolyte at the moment of contact with the diaphragm.
[0140] Thermal shrinkage test: Place the diaphragm in a 130°C forced air oven for 1 hour, and measure the dimensional change of the diaphragm before and after placement.
[0141] Among them, S0 is the area of the diaphragm before heating, and S is the area after shrinkage due to heating.
[0142] At the same time, the diaphragms provided in the embodiments and comparative examples were assembled into lithium metal batteries, and the lithium metal batteries were subjected to performance tests. The performance tests included:
[0143] Ionic conductivity test: Assemble SS‖SS symmetrical cells (i.e., both positive and negative electrodes are stainless steel gaskets), use an electrochemical workstation to perform electrochemical impedance spectroscopy (EIS), obtain the impedance of the diaphragm body, and calculate the ionic conductivity using the following formula.
[0144]
[0145] Where δ is the ionic conductivity, L is the thickness of the membrane, and R b is the diaphragm body impedance, and S is the stainless steel electrode area.
[0146] Lithium ion migration number test: Assemble Li‖Li symmetrical batteries, use an electrochemical workstation to perform steady-state current polarization test, record the current before and after steady-state, and test the impedance before and after polarization. The lithium ion migration number is calculated using the following formula
[0147]
[0148] Among them, I s is the steady-state current, I0 is the initial current, △V is the polarization voltage, R s is the steady-state impedance, and R0 is the initial impedance.
[0149] The results are shown in the following table:
[0150]
[0151]
[0152]
[0153] It can be seen from the above table that the coated diaphragm prepared by the embodiment of the present application has a good pore size and porosity, so that the overall performance of the coated diaphragm is good.
[0154] By comparing Examples 1 to 6, it can be obtained that as the mass ratio of the polymer whose side chains are substituted by anionic side groups and the binder gradually increases, the thermal shrinkage and the electrolyte contact angle become better (both numerically decrease), and at the same time the pore size and porosity will increase, and the lithium ion migration number and the ionic conductivity will first increase and then decrease. The inventors believe that the reason for the existence of this peak may be: due to the addition of polyetheretherketone, anionic side groups are introduced, and after a phase transformation process, the anionic side groups are induced to the polymer surface, thereby accelerating ion migration and increasing the lithium ion migration number. However, with the further increase in the content of polyetheretherketone, the pore size and porosity further increase, and the influence of the pore size and porosity on anion migration occupies a more dominant position, so the ionic conductivity and the lithium ion migration number decrease.
[0155] By comparing Example 7 with Example 1, it can be seen that the ionic conductivity of Example 1 is increased compared with the commercial separator, but the lithium ion migration number has not changed significantly. Without vapor-induced phase separation, the pore size of the prepared coating layer is larger and the porosity is smaller. Although the ionic conductivity of Example 7 is significantly improved compared with Example 1, the lithium ion migration number and thermal shrinkage performance are correspondingly reduced. The inventors analyzed that the reasons may be: See Figure 8 Due to the faster phase separation speed, the adhesion between the coating layer and the PE base film is poor. During the phase separation process, large cracks appear on the surface of the coating layer. The part without cracks is a dense layer. At the same time, the presence of large cracks does not have a significant impact on the migration of ions. Due to the good affinity between the coating material and the electrolyte and the presence of large pore size cracks on the surface, the affinity of the diaphragm electrolyte is improved, thereby increasing its ionic conductivity.
[0156] By comparing Examples 8 to 10 with Example 1, it can be seen that when the humidity of vapor-induced phase separation is in the range of 30% to 98%, the prepared coated diaphragms all have good performance. At the same time, as the humidity of vapor-induced phase separation increases, the pore size and porosity first increase and then decrease, the lithium ion migration number first decreases and then increases, the ion conductivity first increases and then decreases, the electrolyte contact angle first decreases and then increases, and the thermal shrinkage first increases and then decreases. It can be seen that the humidity of vapor-induced phase separation is in a better range of 60% to 80%.
[0157] By comparing Example 11 to Example 13, it can be obtained that as the thickness of the coating layer increases, the larger the porosity and pore size, the smaller the thermal shrinkage, the smaller the electrolyte contact angle, the larger the lithium ion migration number, and the larger the ionic conductivity. The inventor believes that the reason for this phenomenon may be: when the coating thickness increases, at a constant humidity, it takes longer to fully realize the steam-induced phase separation. The phase separation time is extended, the polymer poor phase will grow further (forming a porous structure), the pore size becomes larger, and the porosity increases. The larger pore size reduces the hindrance to the migration of anions and cations, so the ionic conductivity increases, and the lithium ion migration number decreases, but due to the increase in thickness, the lithium migration number increases overall. The larger pore size and porosity make it easier for the electrolyte to penetrate, so the contact angle decreases. The increase in thickness increases the overall thermal stability, so the thermal shrinkage rate decreases.
[0158] It can be seen from the data of Examples 14 to 16 that the value of n / (n+m) is feasible within the range of 0.3 to 1, and its performance is better than that of Comparative Example 1.
[0159] By comparing Examples 17 to 19, it can be obtained that as the gas-induced phase separation time increases, the larger the porosity and pore size, the greater the thermal shrinkage, the smaller the electrolyte contact angle, the smaller the lithium ion migration number, and the larger the ionic conductivity. The inventor believes that the reason for this phenomenon may be: during the vapor phase separation process, as the time is extended, the polymer-poor phase will grow further, the pore size will increase, and the porosity will increase. A larger pore size reduces the hindrance to the migration of anions and cations, so the ionic conductivity increases and the lithium ion migration number decreases. A larger pore size makes it easier for the electrolyte to penetrate, so the contact angle decreases. A larger pore size means a looser coating layer structure. Under the premise of the same adhesion as the base film, a looser structure has worse thermal stability.
[0160] According to the data of Examples 20, 21 and 22, polyetheretherketone with lithium carboxylate side groups can also be implemented. At the same time, the coated diaphragm made of polyetheretherketone with lithium carboxylate side groups can achieve almost the same effect as the coated diaphragm made of polyetheretherketone with lithium sulfonate side groups.
[0161] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A coated diaphragm, characterized in that: The coated diaphragm comprises: a base membrane and a coating layer, wherein the coating layer is attached to at least a portion of the base membrane, the coated diaphragm has a porosity of 52% to 80%, the pore structure of the coating layer has a pore size range of not less than 10 nm, and the coating layer comprises a polymer whose side chains are substituted by anionic side groups.
2. The coated diaphragm according to claim 1, characterized in that The anionic side groups include -COOLi and / or -SO3Li.
3. The coated diaphragm according to claim 1 or 2, characterized in that ,, the polymer is a polar polymer; or The polymer is polyetheretherketone.
4. The coated diaphragm according to any one of claims 1 to 3, characterized in that The structural formula of the polymer whose side chain is substituted by anionic side groups is: Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and n / (n+m)=0.3-1.
5. The coated diaphragm according to any one of claims 1 to 4, characterized in that In the coating layer, the mass proportion of the polymer whose side chains are substituted by anionic side groups is 5%-90%.
6. The coated diaphragm according to any one of claims 1 to 5, characterized in that The coating layer has a thickness of 0.5-20 μm.
7. The coated diaphragm according to any one of claims 1 to 6, characterized in that The coating layer also includes a binder. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyetherimide, poly(m-phenylene isophthalamide) and poly(p-phenylene terephthalamide); and / or The base film is one of a polypropylene microporous membrane, a polyethylene microporous membrane or a polypropylene / polyethylene / polypropylene three-layer composite microporous membrane.
8. A coated diaphragm, characterized in that: The coated diaphragm comprises: a base film and a coating layer, wherein the coating layer is attached to at least a portion of the base film; the coated diaphragm has a porosity of 52% to 80%, and the pore size range of the pore structure of the coating layer is not less than 10 nm; the coating layer comprises a polymer whose side chain is substituted by anionic side groups, and the structural formula of the polymer whose side chain is substituted by anionic side groups is: Wherein, R is -COOLi and / or -SO3Li, m and n are independently selected from any positive integer, and optionally, n / (n+m)=0.3-1.
9. A method for preparing a coated diaphragm, characterized in that: The method comprises: Applying the coating slurry to the surface of the base film to obtain a solution-coated diaphragm; Phase separation is performed on the solution-coated diaphragm to replace the good solvent in the coating slurry, and then drying is performed to obtain a coated diaphragm including a coating layer; Wherein, the phase separation is a combination of steam-induced phase separation and non-solvent-induced phase separation; the coating slurry includes a polymer whose side chains are substituted by anionic side groups, and further, the anionic side groups include -COOLi and / or -SO3Li.
10. The method for preparing a coated diaphragm according to claim 9, characterized in that: The humidity of the steam-induced phase separation is 30%-95%, and the time of the steam-induced phase separation is 10-300s; the poor solvent for the non-solvent-induced phase separation includes at least one of water, ethanol, isopropanol, n-pentanol, ethyl acetate and dichloromethane.
11. The method for preparing a coated diaphragm according to claim 10, characterized in that: The coating slurry comprises a polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group or a polyetheretherketone whose side chain is substituted by a lithium carboxylate-containing side group; The preparation method of the polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group comprises: The polyetheretherketone is subjected to a sulfonation reaction with sulfuric acid to obtain a sulfonated polyetheretherketone; The sulfonated polyetheretherketone and lithium hydroxide are subjected to a lithium salt reaction to obtain a polyetheretherketone whose side chain is substituted by a lithium sulfonate-containing side group; The preparation method of polyetheretherketone whose side chain is substituted by a lithium carboxylate-containing side group comprises: 4,4'-difluorobenzophenone, hydroquinone, methyl hydroquinone and potassium carbonate are subjected to aromatic nucleophilic substitution reaction to obtain polyetheretherketone containing methyl group; Substituting the polyetheretherketone containing methyl to obtain polyetheretherketone containing dibromomethyl; subjecting the polyetheretherketone containing dibromomethyl to a temperature-raising reaction to obtain polyetheretherketone containing aldehyde group; Carrying out an oxidation reaction on the polyetheretherketone containing an aldehyde group to obtain a carboxylated polyetheretherketone; The carboxylated polyetheretherketone is subjected to a lithium salt reaction with lithium hydroxide to obtain a polyetheretherketone whose side chain is substituted by a lithium carboxylate-containing side group.
12. The method for preparing a coated diaphragm according to claim 11, characterized in that: The mass proportion of the solvent in the coating slurry is 50%-90%.
13. A lithium battery, characterized in that: The lithium battery comprises the coated diaphragm according to any one of claims 1 to 8 or a coated diaphragm prepared by the method for preparing the coated diaphragm according to any one of embodiments 9 to 12.
Citation Information
Cited By
Battery monomer and preparation method thereof, battery device and energy storage device
CN122291866A